Vulnerability cloud: A novel approach to assess the vulnerability of critical infrastructure systems. (22nd June 2022) - Meng, Lingpeng; Yao, Xiaobo; Chen, Qian; Han, Chuanfeng
Summary: Critical infrastructures provide citizens with lifeline functions such as water, electricity and energy and so forth. These interdependent infrastructure systems require reliable models for vulnerability measurement and topological controllability against usual disruptions and unusual hazards. This article proposes a novel approach, named vulnerability cloud, to describe vulnerability distribution and assess the vulnerability of critical infrastructure systems. A vulnerability distribution network is developed for simulation of negative impact on each node, with which the results are represented in vulnerability cloud by three metrics of vulnerability. The vulnerability cloud of single‐service and multiservice infrastructure system are proposed, respectively. This approach is applied to a case study of "electric‐gas" interdependent critical infrastructure system. Results show that a node's vulnerability and serviceability is closely related to the node's degree, especially the out‐degree, while overall system's vulnerability is greatly affected by descent rate of coverage of each infrastructural service node. This approach, at the same time, generates probabilistic simulation diagrams to show continuous vulnerability distribution in areas covered by the specified critical infrastructure systems.